2016
DOI: 10.4137/cmo.s40479
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Metastasis and Cachexia in a Patient with Breast Cancer: A Case Study

Abstract: Cachexia, a wasting syndrome associated with advanced cancer and metastasis, is rarely documented in breast cancer patients. However, the incidence of cachexia in breast cancer is now thought to be largely underestimated. In our case report of a breast cancer patient with bone metastasis monitored during the course of her treatment, we document the development of cachexia by image analysis in relation to her metastatic burden. Elucidation of the link between metastatic burden and cachexia could unveil a highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…Although cachexia is generally observed in pancreatic, gastric, colorectal, lung, and head and neck cancer, recent studies have provided a compelling evidence that there is a relationship between advance metastatic breast cancer and cachexia due to a decrease in muscle mass and excessive weight loss (53)(54)(55). Recent studies have also demonstrated that a high level of IL-6 is associated with cachexia, angiogenesis, atrophy, increased catabolism of muscle protein and resistance to treatment in advance breast cancer (2,35,56).…”
Section: Discussionmentioning
confidence: 99%
“…Although cachexia is generally observed in pancreatic, gastric, colorectal, lung, and head and neck cancer, recent studies have provided a compelling evidence that there is a relationship between advance metastatic breast cancer and cachexia due to a decrease in muscle mass and excessive weight loss (53)(54)(55). Recent studies have also demonstrated that a high level of IL-6 is associated with cachexia, angiogenesis, atrophy, increased catabolism of muscle protein and resistance to treatment in advance breast cancer (2,35,56).…”
Section: Discussionmentioning
confidence: 99%
“…According to the latest American Society of Clinical Oncology (ASCO) report on clinical research of cancer, there are now 15 million cancer survivors in the United States; that is, one in every 20 Americans has had or is living with cancer. One of the most common problems facing patients with advanced tumors is cancer cachexia . Evidence suggests that more than half of the patients with malignant tumors could progress to the cancer cachexia stage .…”
Section: Introductionmentioning
confidence: 99%
“…30 Cancer related cachexia is seen in 50-80% of cancer patients with advanced and metastatic disease. 32 Cachexia weakens the body and promotes further spread of cancer. 32 Other most commonly complained physical problem by palliative care patients are: constipation (75%), change of taste (71.7%), lack of concentration (70%) and vomiting (58.3%).…”
Section: Discussionmentioning
confidence: 99%
“…32 Cachexia weakens the body and promotes further spread of cancer. 32 Other most commonly complained physical problem by palliative care patients are: constipation (75%), change of taste (71.7%), lack of concentration (70%) and vomiting (58.3%). Constipation is very common in palliative care patients and affects more than 50% of patients.…”
Section: Discussionmentioning
confidence: 99%